Assessing the Impact of Hydraulic Control Structures on Hydrodynamic Modelling in Shallow Waters - Alfonso Arrieta-Pastrana; Edwin A. Martínez-Padilla; Modesto Pérez-Sánchez; Oscar E. Coronado-Hernández; Helena M. Ramos (Journal of Marine Science and Engineering, 2025)
Currently, hydrodynamic models for bay and estuarine systems involve many parameters that require proper calibration to design coastal structures effectively. However, in coastal regions with limited data availability, the implementation of such models becomes challenging. This research introduces a simplified hydrodynamic methodology designed to analyse the impact of hydraulic control structures in shallow waters. This approach offers a computationally efficient alternative that allows engineers to rapidly evaluate the impact of horizontal and vertical constrictions in shallow waters experiencing wave propagation. A practical application is demonstrated in a one-dimensional channel with a length of 200,000 m and an average depth of 5 m. The only parameter required for calibration in the proposed methodology is bed friction. The three analysed scenarios—longitudinal constriction, plan-view constriction, and the influence of bed friction—demonstrate the model’s sensitivity to these variations, highlighting its reliability as a decision-making tool for coastal engineering projects. Moreover, the comparison of the proposed hydrodynamic simulation methodology at the stabilised tidal inlet structure in Cartagena de Indias, Colombia, demonstrated its ability to reproduce observed water levels accurately, reinforcing its reliability and potential for broader application.